Non-Interest Income and Deposit Money Banks (DMBs) Performance in Nigeria - Lateef Adewale Yunusa; Kareem Abidemi Arikewuyo; Olusola Enitan Olowofela; Wasiu Abiodun Sanyaolu (Signifikan: Jurnal Ilmu Ekonomi, 2022)
The review of the regulations guiding the activities of Deposit Money Banks (DMBs) in Nigeria affected the revenue generated by DMBs, forcing most banks to diversify their sources of revenue to non-interest income. Panel data technique was employed to examine the impact of non-interest income on DMBs performance in Nigeria from 2012 through 2019. The empirical finding revealed that noninterest income, capital adequacy ratio, and bank loan positively and significantly impact DMBs’ performance in Nigeria. The study recommends that DMBs delve into non-interest income activities as it appeared to improve the performance of DMBs in Nigeria, and the monetary authority should review the policy guiding the non-interest income activities of the DMBs at regular intervals.How to Cite:Yunusa, L. A., Arikewuyo, K. A., Olowofela, E. O. & Sanyaolu, W. A. (2022). Non-Interest Income and Deposit Money Banks (DMBs) Performance in Nigeria. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 31-42. https://doi.org/10.15408/sjie.v11i1.15469.